Export Processing Zones in Sub-Saharan Africa - Watson, Peter (World Bank, Washington, DC, 2012)
Attempts in Africa to use Export Processing Zones (EPZ) as an instrument for economic development, with the exception of Mauritius, have been less successful then in countries in East Asia, Central America, and the Caribbean basin. This paper examines the literature on Export Processing and Free Trade Zones. Successful zones in Mauritius, Tangiers, Panama and the Dominican Republic, were visited and investors, developers and government officials in the zones were interviewed in order to determine what were the factors that resulted in their success. The paper concludes that there is substantial potential for African countries to benefit from export-oriented growth based on the development of EPZs. Any country attempting to develop an EPZ program will have to enlist the concerted and coordinated support of its development partners in the implementation of its program.